Quantitative PCR genotyping assay for the Ts65Dn mouse model of Down syndrome - Dong P. Liu; Cecilia Schmidt; Timothy Billings; Muriel T. Davisson (BioTechniques)
The Ts65Dn mouse is a segmentally trisomic model for Down syndrome. Until now, Ts65Dn mice have been identified by the laborious methods of either chromosomal analysis of cultured peripheral lymphocytes or fluorescent in situ hybridization (FISH). We report here a quantitative PCR method for genotyping Ts65Dn mice, as well as a phenotypic description for visually preclassifying mice to be genotyped.